New species of Iragua Melichar, 1926 (Insecta: Homoptera: Cicadellidae) - Lozada, Pedro W. (1998)
A new species of Iragua Melichar, I. chola sp. n., from Tambopata Reserved Zone, Madre de Dios department, and Chanchamayo, Junín department, in Perú, is described and illustrated. The type material is deposited in the collections of the Museo Nacional de Historia Natural and the Museo de Entomología of the Universidad Nacional Agraria La Molina, Lima, Perú.